Emerging airborne contaminants in India: Platinum Group Elements from catalytic converters in motor vehicles. (December 2016) - Sen, Indra S.; Mitra, Arijeet; Peucker-Ehrenbrink, Bernhard; Rothenberg, Sarah E.; Tripathi, Sachchida Nand; Bizimis, Michael
Abstract: Platinum Group Element (PGE) pollution on the Indian subcontinent is a growing concern because vehicle sales in India have rapidly increased over the last decade, and it is well known that automobile catalytic converters are one of the major source of anthropogenic PGE in the environment. Despite the rapid growth of the Indian automobile industry, the sources and magnitude of PGE contamination in Indian airborne particles are unknown. In this study we report PGE and mercury (Hg) concentrations, as well as osmium isotope ratios ( 187 Os/ 188 Os) of airborne particles (PM10 ) collected in Kanpur, a large industrial city in India. We estimate that 61 ± 22%, 32 ± 24%, and 7 ± 3% of the total Os fraction are derived from eroding upper continental crust, catalytic converters fitted in the exhaust system of motor vehicles, and fossil fuel combustion, respectively. Only one sample had a ten times higher (∼76%) than average contribution from fossil fuel. Unlike Os, Pt is predominantly (84 ± 10%) derived from anthropogenic sources. Platinum Group Element and Hg concentrations are not well correlated. However, the highest concentration of particulate Hg corresponds to the most radiogenic 187 Os/ 188 Os isotope ratios (4.6). Our results further indicated that PGE/Ir ratios could be successfully used to quantify the relative proportions of natural and anthropogenic PGE sources in aerosol samples. Since PGE and Hg data on Indian environmental samples are scarce, this study provides an interpretive framework that calls for additional assessments of PGE and Hg concentrations in environmental samples from India. Highlights: Platinum Group Element Pollution is a growing concern in Asia. Osmium isotopes as tracers of PGE sources is proposed. Platinum Group Element pollution in India.